ChemInform Abstract: Boronate Affinity Materials for Separation and Molecular Recognition: Structure, Properties and Applications. Issue 50 (December 2015) - Li, Daojin; Chen, Yang; Liu, Zhen
Abstract: Review: 219 refs.